From boots to books: applying Schlossberg’s transition model to the transition of today’s American veterans to higher education - Ryan, Shawn (Kansas State University, 2010)
Attending college or university immediately after serving on active duty in the U.S. military can be a challenging transition because the daily roles and responsibilities of active duty service members greatly differ from that of college students. Therefore, the purpose of this report is to provide an accurate portrayal of the experiences and challenges veterans encounter when they leave the armed forces and become students at a college or university. The report is a resource that academic advisors and other student affairs professionals can use to increase their awareness and understanding of veterans’ transition experiences from military life to college life. To achieve this goal, the following are included in the report: (a) a theory driven description of veterans’ needs and concerns as they transition from military to college, and available resources that can facilitate veterans’ transitions; (b) questions advisors should ask themselves and their respective institution regarding how they can better serve this population of students; and (c) three case studies of student-veterans who served at least two, but no more than four, years of active duty in the United States Armed Forces, and who chose to enroll in an institution of higher education shortly after their discharge from the military. The four coping mechanisms, or four S’s (Situation, Self, Support, Strategies), of Schlossberg’s Transition Theory (Schlossberg, Waters, & Goodman, 1995) serve as the organizing framework of the report. Although some articles have touched upon Schlossberg’s transition model to the student-veteran transition (DiRamio, Ackerman, & Mitchell, 2008; Livingston, 2009), none used the model as a framework to organize the relevant literature.
Keywords: veteran; transition; Schlossberg; college; student; Education, Guidance and Counseling (0519)